Code Switching in Television Advertisements in Bangladesh: Features and Facts - Akter, Most Salma; Mohiuddin, Mohammad Golam; Joher, Umme Hani M (CenRaPS Journal of Social Sciences, 2024)
Switching codes has been a strategic communication tool in today's world of business and trades, and it is largely noticeable in television advertisements. The paper explores the striking features of code switching and investigate the reasons behind Bangla-English code switching in Bangladeshi television advertisements and its impact on viewers. The study used a mixed method approach for data collection including questionnaire, semi structured interview and observations. The researchers conducted interview of advertising managers, questionnaire survey among students and mass people, and observed various TV channels to collect authentic data. The results reveal that intra-sentential code switching is the most prominently employed type of code switching in television advertisements. The study also finds that code switching is used in television advertisements to attract and engage viewers, bridge lexical gaps, emphasize key points, and enhance contextual understanding. Besides, the results demonstrate that code switching has a notable impact on viewers, enhancing their ability to recall advertisements and influencing their purchasing decisions. The researchers recommend that advertisers should consider the social standing of their intended audience and determine whether code switching aligns well with both the product's image and the social identities of the consumers. Keywords: code-switching, television, advertisement, impact on viewers